Variation of Rainfall with Space and Time in Duhok Governorate - Waleed Al- Rijabo; Diyar Bleej (College of Education for Pure Sciences, 2010)
Abstract Rainfall analysis is important in different domains such as: agricultural planning, water resources plannings, runoff prediction, climatological studies, environmental studies, stream flow estimation and human life activities. Variation of rainfall with space and time were studied in Duhok Governorate, Mean monthly, seasonal and annual values of rainfall were found in different weather stations (Duhok, Zakho, Semel, Zawaite, Sersing, Amedy and Akre station). Winter months represent about 45-55% of the total annual rainfall. The annual variability of rainfall in all these stations are high. Isoheytal method was used to estimate the mean monthly values and mean annual values of rainfall over Duhok Governorate. Simple and Multiple Regression Equation were found between rainfall and different meteorological elements.